Stages of Acquisition and the P/E Model of Working Memory: Complementary or contrasting approaches to foreign language aptitude?. (March 2021) - Wen, Zhisheng (Edward); Skehan, Peter
Abstract: This paper explores the roles of both working memory (WM) and more traditional aptitude components, such as input processing and language analytic ability in the context of foreign language learning aptitude. More specifically, the paper compares two current perspectives on language aptitude: the Stages Approach (Skehan, 2016, 2019) and the P/E Model (Wen, 2016, 2019). Input processing and noticing, pattern identification and complexification, and feedback are examined as they relate to both perspectives and are then used to discuss existing aptitude testing, recent research, and broader theoretical issues. It is argued that WM and language aptitude play different but complementary roles at each of these stages, reflecting the various linguistic and psycholinguistic processes that are most prominent in other aspects of language learning. Overall, though both perspectives posit that WM and language aptitude have equal importance at the input processing stage, they exert greater influence at each of the remaining stages. More traditional views of aptitude dominate at the pattern identification and complexification stage and WM with the feedback stage.